Impact of Import Restrictions Policy on Dairy Supply and Demand in Indonesia - Priyono; R. Nurmalina; Burhanuddin; N. Ilham (Tropical Animal Science Journal, 2023)
Dairy cows are one of the strategic livestock in Indonesia. However, increased dairy demand, which exceeds domestic dairy production, increases dairy import quantity. As dairy import increases, import tariff as an import restriction policy can be used to protect the sustainability of domestic dairy production. This study aimed to investigate the impact of import tariff policy on dairy supply and demand in Indonesia. This study used secondary data obtained from various official institutions. Factors determining dairy supply and demand were estimated using two-stage least squares (2SLS), and the impact of import tariff policy was estimated using a simultaneous equation system model. The empirical results indicate that the import tariff policy has a positive impact on dairy supply and a negative impact on dairy demand. Import tariffs were a factor determining the positive impact on dairy production, dairy cow population, and domestic dairy prices. The import tariff policy also had a negative impact on decreasing the quantity of dairy imports. It is concluded that import tariffs could be an important dairy import restriction policy to protect domestic dairy production and dairy producers in Indonesia.